2006
DOI: 10.1158/1078-0432.ccr-05-1769
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells versus Imaging—Predicting Overall Survival in Metastatic Breast Cancer

Abstract: Purpose: The presence of z5 circulating tumor cells (CTC) in 7.5 mL blood from patients with measurable metastatic breast cancer before and/or after initiation of therapy is associated with shorter progression-free and overall survival. In this report, we compared the use of CTCs to radiology for prediction of overall survival. Experimental Design: One hundred thirty-eight metastatic breast cancer patients had imaging studies done before and a median of 10 weeks after the initiation of therapy. All scans were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
483
1
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(505 citation statements)
references
References 18 publications
12
483
1
9
Order By: Relevance
“…This hypothesis was confirmed by several studies which found a strong correlation between the level of circulating tumor cells (CTCs) and the prognosis of metastatic breast cancer by showing that the number of circulating tumor cells before treatment is an independent predictor of overall survival in patients with metastatic breast cancer [25][26][27]. Also patients who after treatment converted from elevated CTCs to nonelevated levels show a clinical response [28].…”
Section: Total (95% Ci)mentioning
confidence: 73%
“…This hypothesis was confirmed by several studies which found a strong correlation between the level of circulating tumor cells (CTCs) and the prognosis of metastatic breast cancer by showing that the number of circulating tumor cells before treatment is an independent predictor of overall survival in patients with metastatic breast cancer [25][26][27]. Also patients who after treatment converted from elevated CTCs to nonelevated levels show a clinical response [28].…”
Section: Total (95% Ci)mentioning
confidence: 73%
“…Additionally, a change in CTC numbers at first follow-up of therapy is associated with outcome [7,[25][26][27]. Nevertheless, CTCs can be detected in only 60% of the metastatic breast cancer patients, suggesting that there is room for improvement in the CellSearch assay.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of CTC using CellSearch has been cleared by the Food and Drug Administration as a prognostic indicator, in conjunction with other clinical methods, for patients with metastatic breast, prostate, and colorectal cancers. Studies in metastatic breast, colorectal, and prostate cancer showed that patients about to start new lines of chemotherapy could be divided into groups with favourable and unfavourable prognosis on the basis of the number of CTCs measured with the analytically valid CellSearch system(Veridex, Raritan, NJ, USA) [3,[5][6][7][8][9][10][11][12][13]20]. When studying the association between the number of CTCs and evolution of the disease, researchers generally use a single cutpoint to identify favorable and unfavorable response groups, such as 5 CTCs for MBC [3,4,14], three for metastatic colorectal cancer [11], and five for castration resistant prostate cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) have been shown to be an independent prognostic factor in metastatic breast cancer (MBC) [3][4][5][6], in metastatic prostate cancer [7][8][9][10] and in metastatic colorectal cancer [11,12]. They represent a promising tool for therapeutic monitoring: an elevated number of CTCs measured at any time in the clinical course were associated with a high likelihood of a very short time to progression.…”
Section: Introductionmentioning
confidence: 99%